The Implementation of a State-wide Rapid Initiation of Antiretroviral Therapy as a Best Practice in Primary Care Practices Using an Academic Detailing Approach: Lessons Learned from NewYork State, United States - Cabiria Monica Barbosu; Lisette Alcantara; Saloni Sharma; Jahron Marriott; Oksana Babiy; Rebecca Deamer; Marcia Kindlon; Timothy Dye (Global Health and Education Projects, Inc., 2022)
Background: NewYork State Department of Health AIDS Institute policy recommends that primary care clinicians should initiate same-day-antiretroviral treatment (ART) of a new HIV diagnosis or at the next clinical visit as the standard of care. However, non-HIV-specialized primary care clinicians might not be sufficiently trained to initiate a specialized ART with a newly HIV diagnosed patient. We assessed clinicians' knowledge and attitudes toward the rapid initiation of ART and provided academic sessions as a training method to guide clinicians through the implementation of a new standard of care. Methods: A Research Electronic Data Capture (REDCap), Health Insurance Portability and Accountability Act (HIPAA)-compliant, online survey was sent to primary care clinicians to assess their knowledge and attitudes towards Rapid Initiation of ART (RIA). We provided personalized academic detailing sessions, addressing questions and concerns gathered from both the initial survey and the individual pre-assessment questionnaire completed prior to the sessions. Results: The survey was initially distributed in February 2019, followed by 4weekly reminders. Approximately 585 providers completed the survey. Subsequently, 552 health care providers from 25 out of 62 counties in NY State were detailed between March 2019 and March 2021. Lessons learned from the sessions included the identification of pragmatic strategies that could be used in the design of effective detailing sessions, followed by enhanced clinical knowledge, which improved patient care. Conclusion and Global Health Implications: Inconsistencies in the current testing practices result in missed HIV diagnoses and an increased risk of HIV transmission.Academic detailing-training techniques can be used to respond to clinician-identified key issues/attitudes that may result in a new intervention, suggesting a promising approach in addressing the implementation barriers of of rapid-treatment initiation as the standard of care. The academic detailing approach can be easily adapted and can be beneficial in global public health, HIV/ AIDS control, and other conditions that require a medical practice change.   Copyright © 2022 Barbosu et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0.